Perhitungan Waktu (Time Calculation) Fenomena Tanpa Bayangan di Kota Sambas Kalimantan Barat - Reza Akbar (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2019)
The shadow less phenomenon in a city is actually already known by the people in Indonesia. In the City of Sambas, the shadow less phenomenon has not been as popular as in the City of Pontianak. The public perception in general is that phenomenon does not occur in this city, but only in certain cities. This research is a kind of qualitative library research by utilizing secondary data derived from five-year ephemeris data, which are 2019, 2020, 2021, 2022, and 2023. The data collection technique uses documentation techniques derived from ephemeris data which is taken from the Winhisab software. Based on this study, the shadow less phenomenon in the City of Sambas occurs twice a year, in March and September. In March, this phenomenon occurred on the 23rd to 24th or after the vernal equinox. Whereas in September, this phenomenon occurred on the 19th to 20th or before the autumnal equinox. In addition, based on the solar transit time calculation using the mid-WIB time, we get that in September, the time of the shadow less phenomenon in the City of Sambas occurred earlier than March.